2010
DOI: 10.1002/jcb.22724
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relationship Between Cytosolic NADH and ENOX2 Inhibition Triggers Sphingolipid‐Induced Apoptosis in HeLa Cells

Abstract: ENOX2 (tNOX), a tumor-associated cell surface ubiquinol (NADH) oxidase, functions as an alternative terminal oxidase for plasma membrane electron transport. Ubiquitous in all cancer cell lines studied thus far, ENOX2 expression correlates with the abnormal growth and division associated with the malignant phenotype. ENOX2 has been proposed as the cellular target for various quinone site inhibitors that demonstrate anticancer activity such as the green tea constituent epigallocatechin-3-gallate (EGCg) and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The pathway analysis of the down-regulated proteins identified c-Jun as a common regulator and immunoblotting confirmed that phosphorylation of c-Jun was suppressed by VJ115 (Supplemental Figure 2). Recently, De Luca et al [35] have shown that inhibition of ENOX activity and the subsequent increase in NADH resulted in sphingosine kinase inhibition. Su et al [36] found that sphingosine 1-phosphate positively regulates cJun.…”
Section: Discussionmentioning
confidence: 99%
“…The pathway analysis of the down-regulated proteins identified c-Jun as a common regulator and immunoblotting confirmed that phosphorylation of c-Jun was suppressed by VJ115 (Supplemental Figure 2). Recently, De Luca et al [35] have shown that inhibition of ENOX activity and the subsequent increase in NADH resulted in sphingosine kinase inhibition. Su et al [36] found that sphingosine 1-phosphate positively regulates cJun.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to early intervention is based on previous work in cell culture models showing that ENOX2 proteins are required to support the unregulated growth that typifies cancer cells [7]. If the growth function of ENOX2 is blocked for 48 to 72 h, the cancer cells cannot enlarge following division, cannot pass the checkpoint in G1 that monitors cell size and eventually undergo programmed cell death (apoptosis) [22,37,43]. As an early intervention strategy targeted to ENOX2, the herbal mixture of green tea and a powdered efficacious source of chili peppers ( Capsicum species) with levels of capsaicin sufficiently low so as to not cause discomfort (Capsol-T®), emerges as being effective in reducing ENOX2 levels below the limits of detection in greater than 90% of the subjects thus far evaluated when combined with early detection based on ONCOblot® Tissue of Origin Cancer Test results.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to early intervention is based on previous work in cell culture models showing that ENOX2 proteins are required to support the unregulated growth that typifies cancer cells. If the growth function of ENOX2 is blocked for 48 to 72 h, the cancer cells cannot enlarge following division, cannot pass the checkpoint in G 1 that monitors cell size and eventually undergo programmed cell death (apoptosis) (Morré and Morré, 2003b;De Luca et al, 2010) as diagrammed in Figure 1. Among the early intervention strategies under investigation are several targeted to ENOX2, production of ENOX2-directed vaccines being one promising example.…”
Section: Early Interventionmentioning
confidence: 99%